2002
DOI: 10.1093/arclin/17.5.477
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning in obsessive-compulsive disorder, unipolar depression, and schizophrenia

Abstract: The present study investigated whether schizophrenic, unipolar depressive, and obsessive-compulsive psychiatric patients show a distinguishable profile in tasks considered sensitive to frontal lobe functioning. Three psychiatric samples, each comprising 25 patients with little symptomatic overlap, were compared to 70 healthy controls. Participants completed several executive tasks (Wisconsin Card Sorting Test (WCST), verbal fluency, digit span, Stroop, and Trail-Making). Except for age, which was entered as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
106
4
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 0 publications
17
106
4
6
Order By: Relevance
“…Lesions of the dorsolateral PFC in primates, and of the analogous mPFC in rats, specifically impaired performance on ED set-shifting tasks (Birrell and Brown, 2000;Dias et al, 1996). Similar impairment of performance on the WCST was seen in patients with lesions of the dorsolateral prefrontal cortex (Stuss et al, 2000), and in patients suffering from a variety of neuropsychiatric disorders in which mPFC dysfunction has been implicated (Fossati et al, 1999;Goldstein et al, 2002;Moritz et al, 2002). These results indicate that optimal functioning of the mPFC is important in the cognitive processes that underlie attentional setshifting.…”
Section: Discussionmentioning
confidence: 63%
“…Lesions of the dorsolateral PFC in primates, and of the analogous mPFC in rats, specifically impaired performance on ED set-shifting tasks (Birrell and Brown, 2000;Dias et al, 1996). Similar impairment of performance on the WCST was seen in patients with lesions of the dorsolateral prefrontal cortex (Stuss et al, 2000), and in patients suffering from a variety of neuropsychiatric disorders in which mPFC dysfunction has been implicated (Fossati et al, 1999;Goldstein et al, 2002;Moritz et al, 2002). These results indicate that optimal functioning of the mPFC is important in the cognitive processes that underlie attentional setshifting.…”
Section: Discussionmentioning
confidence: 63%
“…Patients with major depression also have widespread executive dysfunctions, including working memory, set-shifting and inhibition processes, even during the euthymic state (Elliott et al 1998;Murphy et al 2001;Harvey et al 2004). Several studies have reported that depressed patients are impaired on verbal fluency tasks (Landro et al 2001;Moritz et al 2002;Ravnkilde et al 2002), Trail Making Tests (Austin et al 1999;Grant et al 2001;Moritz et al 2002), Wisconsin Card Sorting Test (Ilonen et al 2000;Grant et al 2001;Moritz et al 2002), and on the Tower of London task (Beats et al 1996;Elliott et al 1996). There is, however, some inconsistency, the deficit appearing only in endogenous cases in some studies (Austin et al 1999;Rogers et al 2004), while other authors failed to evidence executive functioning deficits in major depression regardless of the severity (Ravnkilde et al 2002).…”
Section: Cognitive Deficits In Major Depressionmentioning
confidence: 99%
“…Findings of Moritz (2002) showed that better performance of OCD clients, when their performance on WCST was compared to schizophrenia and depressive. Previously most of the literature focused on investigating the cognitive deficits in schizophrenia and depressive (Shabbir, & Ali, 2009), very few researches have focused on anxiety disorder regarding IQ, although some researchers have intensively studied executive functioning of OCD (Ji Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…WAIS-R is Intelligence test which requires full concentration if person mental status is disturbed; they cannot perform according to their capacities. In the present study we did not include any neurological test; but previous findings does relate IQ performance of psychiatric group to neuropsychological dysfunctions (Moritz et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation